Psychosocial Factors Predicting Job Search Behaviour of Long-Term Welfare Recipients in the Netherlands. Issue 4 (December 2014) - Varekamp, Inge; Knijn, Trudie; Bos, Peter; van Wel, Frits
In spite of active labour market policies, a considerable number of welfare recipients in the Netherlands are long-term unemployed. In order to investigate the job search behaviour of this group, we developed a model of job search behaviour, inspired by the theory of planned behaviour, expectancy value theory and self-determination theory Survey data relating to 193 individuals receiving welfare benefits for at least one year were collected. A model, consisting of six social-demographic and eight social and psychosocial variables, was tested with hierarchical multiple regression. Seven factors were found to be positively related to job search behaviour: being a non-Western immigrant, having recently started receiving welfare benefits, receiving encouragement in searching for work from an intimate social network, having a job search requirement imposed, having an expectation of finding a job, individual work valence and job search attitudes. Of these, duration of welfare assistance, the encouragement of an intimate social network, work valence and job search attitude appeared to be mediating factors. The article concludes that activation policy might benefit from a combination of improving job searching attitudes, for instance by discussing ideas about the valence of employment and expectations of success or by considering potential barriers to finding employment within social networks, and introducing a clear requirement to search for jobs, in particular for native Dutch, single mothers and people who have been in receipt of benefits for a long period of time. Such policies have been absent in the Netherlands for a long time, priority being given to those with better chances in the labour market.